Flux Simulation and Studies of the First X-Ray Beam of the ThomX Project - Shahed, Hend Saleem (An-Najah National University, 2018)
In the present work, the angular and spectral flux of the Compton backscattering X-ray source of ThomX are investigated. ThomX is a shortened form of Thomson scattering producing hard X-rays. This work was performed through two steps. Firstly, a short computer pro- gram is written by using analytical formulas allowing the calculation of the expected angular and spectral flux of the Compton source as a function of the characteristics of the incoming electron beam. Then, the CAIN program is used to generate Compton photons in order to describe X-ray spectral and angular distributions and check the agreement between the analytical formulas and CAIN simulations. The CdTe detector parameters (the detector size and distance to the end- station), which will be used in ThomX, were also taken into consideration in the calculations. One important feature is that this simulation code can be run by accessing a giant server computer station in LAL. The best electron parameters in ThomX are investigated to allow producing the highest Compton flux in a given energy bandwidth and a given angular aperture. The effect on the Compton flux of both the Compton kinematics and electron beam characteristics are studied. The calibration of the CdTe detector, which is to be used to detect X-ray flux for ThomX, was performed using 57Co as a radioactive source.
محاكاة ودراسة أول شعاع سيني من مشروع تومكس